Jelly Belly Trans-Synaptic Signaling to Anaplastic Lymphoma Kinase Regulates Neurotransmission Strength and Synapse Architecture - Rohrbough, Jeffrey (2012)
In Drosophila the secreted signaling molecule Jelly Belly (Jeb) activates Anaplastic Lymphoma Kinase (Alk), a receptor tyrosine kinase, in multiple developmental and adult contexts. We have shown previously that Jeb and Alk are highly enriched at Drosophila synapses within the CNS neuropil and neuromuscular junction (NMJ) and postulated a conserved intercellular signaling function. At the embryonic and larval NMJ Jeb is localized in the motor neuron presynaptic terminal whereas Alk is concentrated in the muscle postsynaptic domain surrounding boutons, consistent with anterograde trans-synaptic signaling. Here, we show by functional inhibition of Jeb-Alk signaling that neurotransmission is regulated by Jeb secretion. Jeb is a novel negative regulator of neuromuscular transmission. Reduction or inhibtion of Alk function results in enhanced synaptic transmission. Activation of Alk conversely inhibits synaptic transmission. Restoration of wildtype postsynaptic Alk expression in Alk partial loss-of-function mutants rescues NMJ transmission phenotypes and confirms that postsynaptic Alk regulates NMJ transmission. The effects of impaired Alk signaling on neurotransmission are observed in the absence of associated changes in NMJ structure. Complete removal of Jeb in motor neurons, however, disrupts both presynaptic bouton architecture and postsynaptic differentiation. Non-physiologic activation of Alk signaling also negatively regulates NMJ growth. Activation of Jeb-Alk signaling triggers the Ras-MAP kinase cascade in both pre- and postsynaptic compartments. These novel roles for Jeb-Alk signaling in the modulation of synaptic function and structure have potential implications for recently reported Alk functions in human addiction, retention of spatial memory, cognitive dysfunction in neurofibromatosis and the pathogenesis of amyotrophic lateral sclerosis.